The Design, Development And Evaluation Of A Virtual Reality (Vr)-Based Learning Environment: Its Efficacy In Novice Car Driver Instruction - Chen, Chwen Jen (2005)
This study pursues developmental goals (Reeves, 2000; Richey & Nelson, 1996) by focusing on developing a plausible solution to solve a problem in a real context while at the same time constructing a feasible instructional design and development framework that can guide future developmental efforts. The identified learning problem focuses on the understanding of traffic rules for various road scenarios that consist of ordinary roads, different types of road junction and related traffic signs, in which novice car drivers are found to face difficulty in understanding the conventional learning materials, which are in the form of text and two-dimensional static images. An evaluation that employs a quasi-experimental design is then conducted to investigate the effects of the developed learning environment, which is a VR-based learning environment, through the virtual environments on learning; and to investigate the effects of learners’ aptitudes, both spatial visualisation ability and learning style, on learning. The VRbased learning environment employs an instructional design theoretical framework that combines the concept of integrative goal (Gagne & Merrill, 1990) with the constructivist learning environments design model (Jonassen, 1999) to serve as the macro-strategy and employs the design principles derived from the cognitive theory of multimedia learning (Mayer, 2002) to serve as the micro-strategy. This learning environment also adopts the Recursive, Reflective Design and Development (R2D2) model (Willis, 1995; Willis & Wright, 2000) as the instructional development model. The evaluation study employs a multiple-group pretest-posttest quasi-experimental factorial design. A total of 184 Form Four students participate in this study. The study discovers that learners exposed to the Guided VR mode significantly outperform the learners exposed to the Non-Guided VR mode as well as the learners exposed to the Non VR mode